"The Juices of the Body": Ecomasculine Fluidification in Two Stories by Isak Dinesen. (April 2022) - Mortensen, Peter
Gender is a key factor in shaping perceptions of environmental relationships, and moving toward sustainability requires that we rethink dominant ideas about both femininity and masculinity. Danish bilingual author Karen Blixen (1885–1962) wrote cryptic and convoluted stories under the male pseudonym Isak Dinesen, and while there is an abundance of feminist scholarship on Dinesen, her critique of masculine identity and her relevance to the emergent field of ecomasculinity studies have so far gone unnoticed. In this essay, I draw on feminist scholarship and cultural histories of male embodiment, as I analyze fluid masculine corporeality in "The Monkey" (1934) and "Ehrengard" (1962). In both her early and late narratives, I argue, Dinesen pushes back against the 20th century "metallization" of male bodies with baroque narratives and characters whose trajectories begin to produce novel and fruitful understandings of masculinity and the male body in relation to other bodies and the more-than-human world. More specifically, what I label "fluidification" designates recurring moments in Dinesen's writing when corporeal boundaries are breached and male characters find themselves re-manned and re-environed by their bodies' all-too-human participation in "transcorporeal" flows. The male bodies that populate Dinesen's fiction, I find, diverge strikingly from the seamlessly solid, statuesque, and self-enclosed men of steel fantasized by contemporary fascists, communists, futurists, militarists, and machine-age modernists. While the hegemonic ideal of hard, dry, anti-ecological masculinity has persisted and even flourished to the present day, I approach Dinesen's fictions as counterhegemonic sites where alternative earth-friendlier meanings of masculinity can become visible.